The association between mindfulness, resilience, and academic achievement of pharmacy students in Saudi Arabia - Almanasef, Mona; Almaghaslah, Dalia (Frontiers in Public Health, 2024)
Background: Literature suggests that mindfulness and resilience positively impact academic performance. This study was conducted to assess mindfulness and resilience levels among pharmacy students. The study also aimed to explore the relationship between mindfulness and resilience, as well as their effects on GPA, which serves as an indicator of academic performance.The study utilized the Five Facet Mindfulness Questionnaire (FFMQ), a validated tool consisting of 39 items across five domains: observing, describing, acting with awareness, non-judging of inner experience, and non-reactivity. Additionally, the Brief Resilience Scale (BRS), a validated questionnaire with 6 items using a five-point Likert scale, was employed to assess resilience.The average scores obtained from the mindfulness and resilience scales were 3.00 (SD=0.36) and 3.00 (SD=0.65), indicating intermediate levels of resilience and mindfulness respectively. No statistically significant differences were found in mindfulness scores between male and female students, or between students with and without a previous diagnosis of mental health issues. However, a statistically significant higher level of resilience was observed among students who have never been diagnosed with mental health issues compared to those who reported a previous diagnosis. However, females scored significantly higher in the observing domain of mindfulness compared to males, while males scored significantly higher in the acting with awareness domain. Students who had never been diagnosed with mental health issues scored significantly higher in acting with awareness. A significant positive association was found between resilience and mindfulness scores of the students (r=0.45, P<0.001). However, significant positive correlation was found between resilience and describing as well as acting with awareness mindfulness, P<0.05. Assessing the association between student GPA and mindfulness as well as resilience scores showed a weak association.Tailored interventions and programs could be implemented to foster resilience, enhance students' ability to cope, and equip them with tools to bounce back in the face of adversity. Further research could explore other factors that might influence the strength of the relationships between mindfulness and resilience, and student GPA.